Development of a Cost of Goods Manufactured (COGM) for UMKM Rujak Manis Pak Imam Surabaya - Mochammad Arifin; Martinus Sony Eristiawan (CONTABILITA : Journal of Accounting and Finance, 2025)
The purpose of this study is to develop a comprehensive Cost of Goods Manufactured (COGM) model for UMKM Rujak Manis Pak Imam in Surabaya, with the aim of providing accurate unit‐cost information to support pricing and operational decisions. Data were collected through direct observation of production processes, detailed recording of raw material usage, labor time studies, and allocation of manufacturing overhead using the full costing approach. Raw materials accounted for 81 percent of total costs, direct labor comprised 11  percent, and manufacturing overhead represented the remaining 8 percent. The resulting COGM calculation reveals a production cost of Rp 16.354 per portion of rujak manis. This unit‐cost figure enables the business to set competitive selling prices, target desired profit margins, and identify opportunities for cost control—particularly in raw material procurement and labor efficiency. By implementing the developed COGM model, UMKM Rujak Manis Pak Imam can enhance financial transparency, improve decision‑making, and strengthen its long‑term sustainability in the traditional culinary